PESAN DAKWAH DALAM KEMASAN KARTUN: Analisis Semiotik Model Charles Sanders Peirce Pada Halaman Instagram @ustadzabdulsomad_official - Putri Nurbadri Sukanda (STAINU Tasikmalaya, 2023)
Da’wah messages in the form of cartoon packaging have great potential to convey religious messages to the younger generation. Da’wah messages are also religious messages aimed at spreading religious values to the public. Therefore, this research is entitled “Propagation Messages in Cartoon Packages (Semiotic Analysis of Charles Sanders Peirce’s Model on Instagram Page @ustadzabdulsomad_official)”. The purpose of this study was to find out how the contents of the da’wah messages contained in the da’wah animation video on the Instagram @ustadzabdulsomad_official. This research is a qualitative research with Charles Sanders Peirce’s semiotic analysis method which consists of Sign, Object, and Interpretant. This da’wah messages is also divided into aqidah messages, shari’ah messages, moral messages. This data was obtained through descriptive research and watching animated da’wah videos on Instagram. The results of the study show that there are da’wah messages in the da’wah animated videos, including the category of aqidah context, awareness of Allah SWT monitoring in every action. In the context of shari’ah, one can know the urgency of practice and understand the benefits of a practice. And in the moral context it describes the urgency of respecting parents.